Influence of Family Support on Work-Life Balance: Female Entrepreneurs vs. Female Leaders - Sri Ratna Sari Bulan; Ismarli Muis (HUMANITAS published by Universitas Ahmad Dahlan., 2026)
The increasing participation of women in leadership roles across sectors has intensified challenges related to balancing professional and personal responsibilities. This study investigates differences in the effects of family support on work–life balance between women entrepreneurs and women leaders in institutional settings. Data were collected from 476 respondents representing both groups and analyzed comparatively. The findings demonstrate a contextual divergence in the effectiveness of support types. Emotional support exerted a stronger influence on the work–life balance of women leaders in organizational contexts, whereas instrumental support was more critical for women entrepreneurs. Although women entrepreneurs reported higher levels of emotional support, instrumental support proved more effective in facilitating balance between work and personal life. Conversely, women leaders experienced greater access to instrumental support, yet emotional support played a more decisive role in managing work–life demands. These results highlight the heterogeneous nature of support needs across professional contexts and emphasize the importance of a contextualized approach to understanding women’s work–life balance. This study contributes to the literature on gender, leadership, and work–life balance by clarifying context-specific support mechanisms.